Answer:
The solution in second quadrant is (-2,1).
Explanation:
We have two equations and we have to solve them to get two unknowns.
The equations are
x² + y² = 5 ......... (1) and
⇒ x² = 4y ....... (2)
Now, solving (1) and (2) we get
y² + 4y - 5 = 0
⇒ y² + 5x - x - 5 = 0
⇒ (y + 5)(y - 1) = 0
Therefore, y = - 5 or y = 1
Now, for y = - 5, from equation (2), we get x² = 4 (- 5) = - 20 which is not possible.
Hence, y = 1 and then x² = 4, ⇒ x = ± 2.
So the solutions are (2,1) or (-2,1).
Therefore, the solution in the second quadrant is (-2,1). (Answer)